The Influence of the Use of Audio Visual Media and the Ability to Read the Qur'an on Tahfidz Learning Outcomes at Integrated Islamic Private Junior High School - Rahma Safitri Barus; Asnil Aidah Ritonga; Yahfizham Yahfizham (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to determine the use of audiovisual media that can provide examples in memorizing the Qur'an in terms of writing (visual) and pronunciation (audio) so that the learning process will be more meaningful and will affect student learning outcomes. This research was conducted at the Integrated Islamic Private Junior High School in Medan. This research is of the Quasi Experimental type with factorial design (factorial experimental design). The result of this study is that there is an influence on the use of audio-visual media on the learning outcomes of tahfidz at the Integrated Islamic Private Junior High School in Medan. This can be seen from the results of the first hypothesis test which obtained a calculated F score = 27.335 greater than F table = 1.156 and the sign value. 0.000 is smaller than the significance level of 0.05 so hypothesis testing rejects H0 and accepts Ha. Then there is the influence of the ability to read the Qur'an on the results of learning tahfidz at the Integrated Islamic Private Junior High School. There is also an influence on the use of learning media and the ability to read the Qur'an on the learning outcomes.